IMPLEMENTSI PROJECT BASED LEARNING MELALUI MEDIA DIGITAL SCRAPBOOK PADA PEMBELAJARAN SEJARAH KELAS X SMK BASTREN NURUSSALAM - Khoirul Nisa, Ita; Adzkiyak; Ibrahim Hamdani, M. Iqbal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the passive nature and boredom prevalent in history education at SMK Bastren Nurussalam Jember due to conventional, teacher-centered lectures. The research aims to evaluate the implementation of Project Based Learning (PjBL) integrated with Canva-based Digital Scrapbooks, analyze its impact on students' digital literacy and creativity, and identify the supporting and inhibiting factors in its execution. Operating under a post-positivist philosophy, this qualitative descriptive study involved a history teacher and 20 tenth-grade students as research subjects selected through purposive and snowball sampling techniques. Data collection was comprehensively systematically conducted via direct classroom observation, in-depth interviews, and documentation, followed by interactive data analysis including data reduction, data display, and conclusion drawing. The results reveal that the PjBL model systematically transformed history learning across six structured phases, successfully shifting the pedagogical paradigm from teacher-centered to student-centered. The utilization of Digital Scrapbooks significantly enhanced students' 21st-century competencies, advancing their digital literacy from basic tool utilization toward evaluating valid historical sources, while stimulating their creativity through historical visual storytelling. Key supporting factors included adequate computer laboratory infrastructure and students' high affinity for digital tools, whereas short instructional time allocations and uneven technical skills posed minor challenges. Nevertheless, these barriers were effectively mitigated through intensive teacher facilitation and peer-tutoring. In conclusion, the integration of PjBL and Digital Scrapbooks provides a highly successful, active, and meaningful instructional alternative for history education in vocational high schools.